Chronic exposure to cigarette smoke extract upregulates nicotinic receptor binding in adult and adolescent rats. (15th December 2020) - Cano, Michelle; Reynaga, Daisy D.; Belluzzi, James D.; Loughlin, Sandra E.; Leslie, Frances
Abstract: Heavy smokers display increased radioligand binding of nicotinic acetylcholine receptors (nAChRs). This "upregulation" is thought to be a contributing factor to tobacco dependence. Although cigarette smoke contains thousands of constituents that can contribute to nicotine dependence, it is not well understood whether non-nicotine constituents contribute to nAChR upregulation. In this study, we used an aqueous cigarette smoke extract (CSE), which contains nicotine and soluble constituents of cigarette smoke, to induce nAChR upregulation in adult and adolescent rats. To do this, male rats were exposed to nicotine or CSE (1.5 mg/kg/day nicotine equivalent, intravenously) daily for ten days. This experimental procedure produces equivalent levels of brain and plasma nicotine in nicotine- and CSE-treated animals. We then assessed nAChR upregulation using quantitative autoradiography to measure changes in three nAChR types. Adolescents were found to have consistently greater α4β2 nAChR binding than adults in many brain regions. Chronic nicotine exposure did not significantly increase nAChR binding in any brain region at either age. Chronic CSE exposure selectively increased α4β2 nAChR binding in adolescent medial amygdala and α7 binding in adolescent central amygdala and lateral hypothalamus. CSE also increased α3β4 nAChR binding in the medial habenula and interpeduncular nucleus, and α7 binding in the medial amygdala, independent of age. Overall, this work provides evidence that cigarette smoke constituents influence nAChR upregulation in an age-, nAChR type- and region-dependent manner. Highlights: Adolescents display higher nAChR binding compared to adults in many of the same regions. Cigarette smoke extract upregulates nAChR binding in an age-, subtype- and region-dependent manner. Chronic cigarette smoke extract produces greater changes to nAChRs compared to chronic nicotine alone.